The Effects of Exchange Rate, Interest Rate and Money Supply on Inflation Rate of Lao PDR - sirivongsa, douangkham; CHANTHAVONE , Thongphanh; XIONGTOUA, Tongvang; SIOUDOMPHAN, Soutthavone; HER, Pheng (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The study examines the impact of exchange rate, interest rate, and money supply on the inflation rate in Lao PDR using time series data from 2000-2023. The analysis used a multiple regression model and found that exchange rate and money supply have a similar effect on inflation rates, with a statistical level of 0.01 and 0.05 respectively. The interest rate was not statistically significant. However, the exchange rate has a greater impact than the money supply. If the exchange rate increases by 1%, it results in an increase in the inflation rate of 22.107%, while a decrease results in a decrease. Conversely, if the money supply increases by 1%, it causes an increase in the inflation rate of 0.262%, and vice versa. This indicates that the exchange rate is the most significant factor affecting the inflation rate in Lao PDR. However, the constant value is negative and the statistical significance level is 0.01, suggesting that other factors may also reduce the inflation rate. Therefore, these factors should be considered for further researchers.